Tribocorrosion behavior of novel nickel-free lean duplex stainless steel manufactured via laser-based powder bed fusion - Anand, Abhinav (My University, 2024)
Laser-based powder bed fusion of metals (PBF-LB/M) is an additive manufacturing technology gaining attention in various industries due to its ability to allow design flexibility to fabricate complex structures precisely. In the marine sector, there is a growing interest in PBF-LB/M because of its potential to produce components such as heat exchangers, propeller shafts, impellers, and exhaust manifolds with lesser lead time, reduced cost, and customization. While 316L stainless steel has been a popular choice for marine applications due to its excellent corrosion resistance in seawater atmosphere, nickel-free duplex stainless steel (NiFDSS) emerges as a cost-effective and lightweight alternative, prompting research into its suitability for PBF-LB/M fabrication. This thesis investigates the optimization of process parameters in PBF-LB/M of NiFDSS to attain defect-free samples. Experimental analyses focus on understanding the microstructural transformations of NiFDSS, transitioning from a fully ferritic to a duplex microstructure post-heat treatment. The study evaluates the tribological and corrosion properties of NiFDSS using a tribocorrosion setup under an artificial seawater environment. Results obtained in this study indicate a relative density achievement of 98.83% for PBF-LB/Med NiFDSS. Corrosion testing reveals superior corrosion resistance of NiFDSS, both in its as-built and heat-treated condition, compared to 316L. However, 316L exhibits better wear resistance characteristics. Further process optimization is needed to enhance the wear behavior of NiFDSS samples. Overall, the study underscores the potential of NiFDSS as a viable alternative for marine components, particularly in applications where the wear rates are not very high, leveraging the design flexibility of PBF-LB/M to meet industry demands effectively.
Keywords: Additive manufacturing, 3D printing, Laser-based powder bed fusion, Nickel-free stainless steel, Lean duplex steel, Tribology, Corrosion, Tribocorrosion, Heat treatment, Phase transformation